Association of early childhood caries with risk factors at community homes of Instituto Colombiano de Bienestar Familiar in Zipaquirá, Colombia - Carmenza Macías-Gutiérrez; Diana Marcela Díaz-Quijano; Martha Lucía Caycedo-Espinel; Francisco Lamus-Lemus; Carlos Javier Rincón-Rodríguez (Universidad de Antioquia, 2016)
Introduction: the goal of this study was to establish the association of social and biological risk factors with early childhood caries (ECC) in children from community homes of Instituto Colombiano de Bienestar Familiar (ICBF) in Zipaquirá, Colombia. Methods: descriptive cross-sectional study conducted by universities in 546 children aged 24 to 60 months. The following conditions were identified: socio-demographic variables, hygiene habits, O'Leary index and DMFT index, anthropometric variables, and psychomotor development. To evaluate the association of early childhood caries and severe caries to the variables under study, the Pearson's Chi-squared test was used for categorical variables, and the Spearman's correlation coefficient test was used for ordinal variables. Results: prevalence of ECC of 64.3% (95% CI 60.3%-68,3%) and severe ECC of 54% (95% CI 49.8%-58,2%). There was statistically significant association between the presence of ECC and inadequate brushing, visits to the dentist, dental treatment, the presence of malnutrition and the consumption of food at night after brushing; and severe ECC was associated with visits to the dentist, dental treatment, bottle feeding during the evening, the use of sweeteners in baby bottles, the habit of sleeping with the bottle, and food intake in the evening after brushing. Conclusions: the prevalence of EEC is high. The results of this study help validate the need for a comprehensive approach to children's health care, incorporating ECC to the spectrum of childhood diseases prevalent in the studied population.